1997
DOI: 10.1002/(sici)1097-0142(19970815)80:4<776::aid-cncr17>3.0.co;2-q
|View full text |Cite
|
Sign up to set email alerts
|

Expression of the endogenous galactose-binding protein galectin-3 correlates with the malignant potential of tumors in the central nervous system

Abstract: Galectin-3 expression correlates with the malignant potential of tumors in the central nervous system.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
81
2
2

Year Published

1999
1999
2013
2013

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 154 publications
(92 citation statements)
references
References 23 publications
7
81
2
2
Order By: Relevance
“…H-Ras and galectin-1 are members of two families of proteins known to be associated with human malignancies (Andre et al, 1999;Barondes et al, 1994;Bresalier et al, 1997;Hadari et al, 2000;Kopitz et al, 1998;Ohannesian et al, 1995;Polyak et al, 1997;van den Brule et al, 1995;Wells and Mallucci, 1991;Yamaoka et al, 1991Yamaoka et al, , 2000. Perhaps it is not less important to note that both Ras proteins (Bar-Sagi and Hall, 2000;Downward, 1998;Shields et al, 2000) and galectins (Hughes, 1999;Perillo et al, 1998), share in common a number of regulatory activities including regulation of cell growth, apoptosis, cell adhesion cell migration and metastasis.…”
Section: Discussionmentioning
confidence: 99%
“…H-Ras and galectin-1 are members of two families of proteins known to be associated with human malignancies (Andre et al, 1999;Barondes et al, 1994;Bresalier et al, 1997;Hadari et al, 2000;Kopitz et al, 1998;Ohannesian et al, 1995;Polyak et al, 1997;van den Brule et al, 1995;Wells and Mallucci, 1991;Yamaoka et al, 1991Yamaoka et al, , 2000. Perhaps it is not less important to note that both Ras proteins (Bar-Sagi and Hall, 2000;Downward, 1998;Shields et al, 2000) and galectins (Hughes, 1999;Perillo et al, 1998), share in common a number of regulatory activities including regulation of cell growth, apoptosis, cell adhesion cell migration and metastasis.…”
Section: Discussionmentioning
confidence: 99%
“…3C) using galectin-3 antisense RNA (galectin-3 AS). Previous experiments showed that galectin-3 AS specifically down-regulates the expression of galectin-3 (33) but not of galectin-1 (21). We co-transfected the cells with galectin-3 AS and GFP-K-Ras or GFP-H-Ras, then stimulated the co-transfectants with EGF and measured the time-dependent change in Ras-GTP levels.…”
Section: Galectin-3 Augments the Basal And Egf-induced Increase In Gfmentioning
confidence: 99%
“…Galectin-3 is present in abnormally high levels in many cancers and plays an important role in the growth, survival and spread of cancer cells (Bresalier et al, 1997;Johnson et al, 2007). Galectin-3 is highly expressed on tumor cell surfaces and a variety of metastatic cancer cells and is closely related to cell to cell adhesion, aggregation of cancer cells in vitro, tumor growth and metastasis in vivo (Bresalier et al, 1997;Dumic et al, 2006;Krzeslak and Lipinska, 2004). A notable feature of galectin-3 is its implication in neoplastic transformation and cancer progression.…”
Section: Pectin Mcp and Their Molecular Interaction In Cancermentioning
confidence: 99%